Rare bird documentation form for Northern Goshawk at Cedar Falls, 1998 - Moore, Francis L.et al (1998)
Rare bird documentation form for a Northern Goshawk at Cedar Falls in Black Hawk County, IA on December 20, 1998. Epson - sheet feed